Lennox-gastaut syndrome in a pediatric patient with prader-willi syndrome: A case report and review - Raidah Albaradie; Sharook Alhawaj; Wojod Alothman; Shahid Bashir (Brain Disorders)
Prader-Willi Syndrome is typically caused by paternal deletion of chromosome 15q11-q13. It involves multiple systems and is commonly associated with hypotonia, global developmental delay, and endocrine abnormalities. Seizures are less frequently reported in individuals with Prader-Willi syndrome. Here, we present a rare case of a 3-year-old boy presenting with early-onset tonic seizures, global developmental delay, and an EEG showing a Lennox-Gastaut Syndrome-like pattern. Notably, brain MRI results were normal. This case represents previously unreported co-occurrence of Lennox-Gastaut Syndrome in a pediatric patient with Prader-Willi Syndrome.